Exosome Production Is Key to Neuronal Endosomal Pathway Integrity in Neurodegenerative Diseases - Mathews, Paul M.; Levy, Efrat (Frontiers in Neuroscience, 2019)
Dysfunction of the endosomal–lysosomal system is a prominent pathogenic factor in Alzheimer’s disease (AD) and other neurodevelopmental and neurodegenerative disorders. We and others have extensively characterized the neuronal endosomal pathway pathology that results from either triplication of the amyloid-β precursor protein (APP) gene in Down syndrome (DS) or from expression of the apolipoprotein E ε4 allele (APOE4), the greatest genetic risk factor for late-onset AD. More recently brain exosomes, extracellular vesicles that are generated within and released from endosomal compartments, have been shown to be altered in DS and by APOE4 expression. In this review, we discuss the emerging data arguing for an interdependence between exosome production and endosomal pathway integrity in the brain. In vitro and in vivo studies indicate that altered trafficking through the endosomal pathway or compromised cargo turnover within lysosomes can affect the production, secretion, and content of exosomes. Conversely, exosome biogenesis can affect the endosomal–lysosomal system. Indeed, we propose that efficient exosome release helps to modulate flux through the neuronal endosomal pathway by decompressing potential “traffic jams.” Exosome secretion may have the added benefit of unburdening the neuron’s lysosomal system by delivering endosomal–lysosomal material into the extracellular space, where other cell types may contribute to the degradation of neuronal debris. Thus, maintaining robust neuronal exosome production may prevent or mitigate endosomal and lysosomal abnormalities linked to aging and neurodegenerative diseases. While the current evidence suggests that the exosomal system in the brain can be modulated both by membrane lipid composition and the expression of key proteins that contribute to the formation and secretion of exosomes, how exosomal pathway-regulatory elements sense and respond to perturbations in the endosomal pathway is not well understood. Based upon findings from the extensively studied DS and APOE4 models, we propose that enhanced neuronal exosome secretion can be a protective response, reducing pathological disruption of the endosomal–lysosomal system in disease-vulnerable neurons. Developing therapeutic approaches that help to maintain or enhance neuronal exosome biogenesis and release may be beneficial in a range of disorders of the central nervous system.